Early enforced mobilisation following surgery for gastrointestinal cancer: feasibility and outcomes. Issue 1 (March 2016) - van der Leeden, M.; Huijsmans, R.; Geleijn, E.; de Lange-de Klerk, E.S.M.; Dekker, J.; Bonjer, H.J.; van der Peet, D.L.
Abstract: Objectives: To evaluate the feasibility and outcomes of early enforced mobilisation following surgery for gastrointestinal cancer. Design: Feasibility study with a separate-sample pre–post-test design. Setting: Surgical gastrointestinal ward. Participants: Patients with various types of gastrointestinal cancer, before and after implementation of postoperative enforced mobilisation ( n = 55 and n = 61, respectively). Intervention: The enforced mobilisation protocol included structured mobilisation by a nurse and walking supervised by a physiotherapist, starting within 24 hours of surgery. Main outcome measures: The enforced mobilisation protocol was deemed to be feasible if at least 50% of patients were able to walk the scheduled distance on postoperative day 1. Pre- and postimplementation differences in postoperative pulmonary complications (PPCs), length of hospital stay (LOS) and re-admission rate were analysed using regression analyses, adjusting for relevant co-variables. Results: In the various surgical groups, between 48% and 56% of patients were able to walk the scheduled distance on postoperative day 1, which was regarded as feasible. However, none of the patients who had undergone oesophageal resection were able to walk on postoperative day 1. Excluding these patients from the analyses, a significant decrease in PPCs was found (odds ratio 0.08, 95% confidence interval 0.010 to 0.71, P = 0.023) following implementation of enforced mobilisation. Differences in LOS and re-admission rate were not significant. Conclusions: Early enforced mobilisation seems to be feasible in patients following surgery for gastrointestinal cancer, except for those undergoing oesophageal resection. The occurrence of PPCs was reduced after implementation of enforced mobilisation. Further research is needed to confirm these results.